A new synonym species with description of a new species of Rhopalopsole from China (Plecoptera: Leuctridae). Issue 1 (31st December 2022) - Yu-Ben, Y.; Yu-Zhou, D.
Abstract: Recently, we reviewed the specimens belonging to Rhopalopsole we have collected and compared them with the holotype and paratypes of Rhopalopsole vespertilio Chen & Du, 2017. We found that R. vespertilio should be synonymized with R. xui Yang, Li & Zhu, 2004. Additionally, a new species of the genus Rhopalopsole, R. nanlinga sp. nov . from Guangdong Province of southwestern China, is described and illustrated. The new species is compared to the Rhopalopsole vietnamica west group.